Macroinvertebrates associated with Limnoperna fortunei (Dunker, 1857) (Bivalvia, Mytilidae) in Río de la Plata, Argentina - Darrigran, Gustavo Alberto (1998)
Fil: Darrigran, Gustavo Alberto. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina